Complete response of squamous cell carcinoma of the lung following treatment with pembrolizumab in an elderly patient: A case report. Issue 2 (10th November 2020) - Takeuchi, Eiji; Okamoto, Yuri; Takahashi, Naoki; Morizumi, Shun; Toyoda, Yuko; Kuroda, Naoto; Yorita, Kenji
Abstract : Complete response of non–small cell lung cancer (NSCLC) with immune checkpoint inhibitor (ICI) monotherapy is rare. Here, we encountered an elderly patient who showed complete response of NSCLC following treatment with pembrolizumab. An 84‐year‐old man with a history of bloody sputum for several weeks visited a general physician. At that time, a chest X‐ray revealed a tumor shadow in the left middle lung field, and the patient was referred to our hospital. Following transbronchial biopsy, he was diagnosed with squamous cell carcinoma of the lung. Expression of programmed death ligand 1 (PD‐L1) in tumor cells was 80% or more by immunostaining. Based on the above, immunotherapy with pembrolizumab was performed as first‐line therapy. The cancer cells completely disappeared at the end of the fifth cycle. There were no side effects during the therapeutic course. Treatment with pembrolizumab continued for two years and was then discontinued at the patient's request. Since then, no tumor recurrence has been detected for about one and a half years without treatment. There have been few reports of lung cancer disappearing after treatment with pembrolizumab. In conclusion, in elderly NSCLC patients with PD‐L1 expression of 50% or more, pembrolizumab should be considered as first‐line treatment with the treatment period, and mechanism suggested in this report. Abstract : Here, we present a case of an elderly patient who had a complete response of non–small cell lung cancer (NSCLC) following treatment with pembrolizumab. The complete response was maintained for one and a half years after discontinuation of two years of treatment. In elderly patients with NSCLC with PD‐L1 expression of more than 50%, pembrolizumab should be considered as first‐line treatment with the treatment period, and mechanism suggested in this report.